The development of healthcare mobile robot for helping medical personnel in dealing with COVID-19 patients - Nova Eka Budiyanta; Linda Wijayanti; Widodo Widjaja Basuki; Harlianto Tanudjaja; V. Budi Kartadinata (Indonesian Journal of Electrical Engineering and Computer Science, 2021)
Coronavirus disease (COVID-19) pandemic has succeeded in shaking the whole world. This situation requires medical personnel to work extraordinarily to treat COVID-19 patients with very high risk of transmission. For this reason, this study aimed to helping medical personnel handle COVID-19 patients through robotic technology. The development method in this study is proposed as a way to develop robots to serve patients in isolation rooms controlled at a distance away from other rooms. From technical testing, the movement of the robot with a load of 12.59 kg only experienced a speed slowdown which was not too significant, namely at 0.43s with an average percentage of slowdown of 8.96%. The accuracy of the proximity sensor testing is close to perfect with an accuracy percentage of 99.62%. The robot control distance was monitored and running well. Also, the increase in motor temperature is not too large, supported by measurement results of 32.13%. From non-technical testing, based on the test results of the feasibility test of all respondents with 25 indicators reached a feasibility level of 91.46%. In other words, healthcare mobile robots developed for helping medical personnel in dealing with COVID-19 patients are very feasible to be applied in hospitals.